Effects of wind energy development on survival of female greater prairie-chickens - Winder, Virginia L.; McNew, Lance B.; Gregory, Andrew J.; Hunt, Lyla M.; Wisely, Samantha M.; Sandercock, Brett K. (My University, 2014)
The potential effects of wind energy development on wildlife have received increased attention over the past decade. In Kansas, optimal sites for wind energy development often overlap with preferred habitats of greater prairie-chickens Tympanuchus cupido. Our goal was to determine whether wind energy development affected survival of female prairie-chickens in a grassland ecosystem, assessing one potential impact of wind on an upland gamebird of conservation concern. We focused primarily on the response of female prairie-chickens to wind energy development because population dynamics of prairie-chickens are primarily determined by female demography. We monitored prairie-chickens at a wind facility in Kansas during a 2-year pre-construction (2007–2008) and a 3-year post-construction period (2009–2011). We used data from 220 radio-marked females to calculate weekly survival and hazard rates. We used cause of death for 81 mortality events to test for changes in the proportion of mortalities attributed to mammalian predators, avian predators and collisions. We observed an unexpected increase in annual survival during the post-construction period (0·57) compared with the pre-construction period (0·32). Distance from home range centroid to the nearest wind turbine site had no effect on weekly survival of females. Collision mortality events were rare, and most were associated with fences or transmission lines and not turbine blades. Most female mortality was due to predation (c. 90%). Differences in annual survival were driven by a higher risk of mortality during lekking activity in March and April during the pre-construction period (weekly hazard rate = 0·050–0·062) compared with the post-construction period (hazard rate = 0·012–0·021). We observed no change in the proportion of mortalities attributed to different causes between the two treatment periods. Synthesis and applications. Development of a wind energy facility had no negative effect on survival of female prairie-chickens. The results of our field study indicate that greater prairie-chickens are less sensitive to wind energy development than lesser prairie-chickens Tympanuchus pallidicinctus and greater sage-grouse Centrocercus urophasianus are to oil and gas development. We have strong evidence that survival increased after wind energy development, and hypothesize that energy development affected the local predator community, resulting in an indirect effect of decreased predation risk during the post-construction period.
Keywords: Collisions; Grassland bird community; Grouse; Hazard function; Mortality; Wind turbine